The Church and Mental Health: Theological and Practical Responses - Ryan, Ben (Zygon, 2018)
Over the past few years, the number of Christian projects and charities working in the mental health sector in the United Kingdom has increased dramatically. At the same time, scientific and medical understandings of mental health have been advancing rapidly. These parallel trends beg a serious question: is the Christian Church's response to mental health authentically engaging with a changing scientific picture? Are theological questions like responsibility, sin, redemption, and reconciliation taking account of a changing landscape? This is not a theoretical question, but has major practical consequences for developing practical pastoral responses.